طريقة تعلم مهارة القراءة على النظرية الاجتماعية المعرفية لألبرت باندورا في معهد "التوفيق" السلفي بداو - مالانج. - Istiqomah, Rosyida (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2021)
In the teaching and learning process must be accompanied by learning methods that can attract students so that enthusiasm in participating in learning, the activities chosen must be able to bridge between the knowledge that has been owned by students with new knowledge that will be received by students, especially to develop skills in incorrect language skills only reading skills of students. The bridging things are required to be able to process students' knowledge by seeing the models around them, one of which is by seeing the instructor himself. As a student who always pays attention to the movements of the instructor when teaching. The slightest thing done by the teacher will always be considered even imitated by his students. That is what makes students get lessons from how to pay attention to a model, just like the theory that was expressed by Albert Bandura who is a psychologist who emphasizes the importance of students in processing knowledge from observing the model around. The research method used is a qualitative method with a case study approach that focuses on one particular object to be studied in-depth to be able to uncover the reality behind the phenomenon. So that the data collection techniques, researchers use observation, interviews, and documentation. While data analysis techniques are via descriptive data analysis techniques, namely data reduction, data exposure, and conclusion drawing. The results obtained in this study are a combined method used in Attaufiq Salafiyah Islamic boarding school which combines the harfiyyah, soutiyyah, syllable, syllable, word method, and sentence method methods. The learning process uses four stages by following the four elements of Albert Bandura's social theory, namely the stage of attention when the teacher starts the lesson with greetings and questions students, the second stage is the stage of remembrance when associating new information with old information and expanding and detailing the material, the stage the third is the imitation stage when oral practice and giving homework to students, and the last is the motivation stage by giving praise to students to be more enthusiastic in learning.